Method for preparing nanoscale Al-TiB2 pure-phase intermediate alloy through ball-milling-assisted self-propagating method
The nanoscale Al-TiB2 pure phase intermediate alloy was prepared by ball mill assisted self-propagation method, which solved the problems of large particle size and poor particle size distribution uniformity in traditional methods, and achieved efficient preparation and excellent strengthening performance of nanoscale TiB2 particles.
Patent Information
- Application Number
- CN202411553538.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-02
- Publication Date
- 2025-03-28
AI Technical Summary
In the preparation of nanoscale Al-TiB2 intermediate alloys, the prior art has problems such as large particle size, poor particle size distribution uniformity, poor morphology, and easy particles to aggregate, resulting in insufficient strengthening ability and poor interfacial bonding.
The ball mill assisted self-propagation method was used to activate and pretreat the elemental Ti and B reaction powders through the ball milling process to prepare high-energy storage activated Ti-B precursor powders, and promote self-propagation reactions in the aluminum melt. Finally, nano Al-TiB2 pure phase intermediate alloy was prepared through traditional casting technology.
Effective control of the particle size and morphology of nano-scale TiB2 particles is achieved, the product is pure, the particle size is uniformly distributed, the morphology is regular, and the strengthening ability and the degree of interface bonding are significantly improved.
Smart Images

Figure HDA0005115737030000011 
Figure HDA0005115737030000012 
Figure HDA0005115737030000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of master alloys, and in particular relates to a method for preparing a nano-scale Al-TiB2 pure-phase master alloy with uniform particle size distribution. Background Art
[0002] TiB2 particles have low density, low thermal expansion coefficient, high modulus and good coherence with the aluminum matrix, making them the most widely used strengthening particles for aluminum-based composite materials. At present, the TiB2 strengthening particles commonly used in the industry are mainly divided into micron and nanometer sizes. Since the micron-sized TiB2 particles are large in size and have poor interface bonding with the aluminum matrix, the addition of micron-sized TiB2 particles will reduce the plastic toughness of the aluminum matrix. Compared with micron-sized TiB2 particles, nano-sized TiB2 particles have the advantages of strong strengthening ability and good interface bonding, so they can achieve comprehensive improvement in strength and plasticity. At present, due to the backward production conditions and technical level, the nano-sized TiB2 particles prepared by the endogenous method have problems such as large particle size, poor uniformity of particle size distribution, substandard particle morphology and easy aggregation of particles. At present, nano-sized Al-TiB2 master alloys are prepared in industry by mechanical alloying, mixed salt reaction and single substance powder reaction. The production process of the mixed salt reaction method is mainly as follows: K2TiF6 and KBF4 are added to the aluminum melt at 750℃-850℃, and mechanical stirring is applied to prepare a nano-scale Al-TiB2 master alloy. There are unreacted molten salts on the surface of the nano-scale TiB2 particles prepared by the mixed salt method, which will seriously deteriorate the degree of interfacial bonding between the particles and the aluminum matrix, and ultimately reduce the strengthening ability of the nano-scale TiB2 particles. The single-substance powder reaction method is based on self-propagating reaction. Nano-scale TiB2 particles are directly generated in the melt through the diffusion of Ti and B atoms, and combined with traditional casting technology, a nano-scale Al-TiB2 master alloy is finally prepared. The production process of the single-substance powder reaction method is mainly as follows: Ti powder and B powder are added to the aluminum melt at 800℃-900℃, and mechanical stirring is applied to finally prepare an Al-TiB2 master alloy with a clean surface and good interfacial bonding. However, due to the violent reaction process of the single substance powder reaction method, the high reaction temperature and the long diffusion distance of the reaction powder, the TiB2 prepared by this method has problems such as large particle size, poor particle size distribution uniformity and poor particle morphology. In order to prepare TiB2 ceramic particles with pure products, uniform particle size distribution and good morphology, various methods have been tried at home and abroad to improve the above problems, but the main disadvantages are low preparation efficiency and poor improvement effect.
[0003] The present invention uses single-substance Ti and B powder as the original reaction powder, and adopts a new ball milling-assisted self-propagating method to prepare a nano-scale Al-TiB2 master alloy with pure products, small particle size and uniform distribution. The new ball milling-assisted self-propagating method uses a ball milling process to perform activation pretreatment on single-substance Ti and B reaction powders. First, mechanical energy is transferred to powder internal energy through the continuous collision between the grinding ball and the powder to prepare a high-energy storage activated Ti-B precursor powder, and then the activated powder is pressed into aluminum melt, and a self-propagating reaction is triggered in a high-temperature melt environment, and finally a nano Al-TiB2 pure phase master alloy is prepared through a traditional casting process. Since the present invention pre-activates the Ti and B reaction powders through a ball milling process, the activated Ti-B precursor powder can trigger a self-propagating reaction at a relatively low temperature, effectively reducing the severity of the self-propagating reaction, and promoting the degree of completion of the reaction, and finally achieving effective control of the particle size and morphology of nano TiB2 particles. Summary of the invention
[0004] The present invention adopts ball milling assisted self-propagating method and utilizes B powder, Ti powder and Al powder which are widely available as raw materials to develop a nano-scale Al-TiB2 pure phase intermediate alloy which has an environmentally friendly preparation process, clean products, small particle size and uniform distribution.
[0005] To solve the above problems, the main technical solution of this patent is: to use ball milling assisted self-propagating reaction preparation process, that is, to use ball milling process to activate the original reaction powder and prepare activated Ti-B precursor powder, and combine it with traditional self-propagating reaction to achieve effective control of the particle size and morphology of nano TiB2 particles.
[0006] A nano-scale Al-TiB2 pure phase master alloy prepared by ball milling assisted self-propagating method, the physical phase composition includes α(Al) and TiB2. The preferred average particle size of TiB2 is 210nm, the particle size distribution is 150-250nm, the particle size distribution of TiB2 is uniform, and the morphology is regular.
[0007] Weigh the reaction powder Ti powder, B powder, Al powder and aluminum ingot as required, wherein the molar ratio of Al powder: Ti powder: B powder = (1.0-2.5): (0.5-2.0): (1-4), and the purity of the aluminum ingot is 99.9%. The mass percentage of the aluminum ingot is: 90.5-93.0%, and the total mass percentage of Al powder, Ti powder and B powder is 6%-9.5%. Its particle size and morphology are significantly better than the Al-TiB2 master alloy prepared by the traditional method, and the preparation process is simple, and it is easy to prepare nano Al-TiB2 master alloys with excellent size and morphology on a large area, which has good practical value. The preparation method of the above-mentioned master alloy, the original reaction powder Ti-B powder is pre-activated by ball milling process, and combined with the traditional self-propagating reaction method, finally realizes the controllable preparation of nano TiB2 particle size and morphology, which specifically includes the following steps:
[0008] (1) Raw material preparation: weigh Al powder, Ti powder and B powder according to the required proportion, wherein the molar ratio of Al powder: Ti powder: B powder = (1.0-2.5): (0.5-2.0): (1-4), preferably the molar ratio of Ti powder: B powder is 1:2, wherein the particle size of Al powder is 20-30 μm, the particle size of Ti powder is 30-50 μm, the particle size of B powder is 1-20 μm, the purity is (96%), and the purity of aluminum ingot is 99.9%;
[0009] (2) Mixing: Place Ti powder and B powder in a mixer and mix them evenly;
[0010] (3) ball milling activation treatment, the uniformly mixed Ti powder and B powder are placed in a stainless steel vacuum ball mill, the gas in the ball mill is extracted by a vacuum pump, and vacuum dry ball milling is performed using ZrO2 grinding balls in a planetary high-energy ball mill, wherein the ball milling time is 10 to 50 hours, the ball-to-material ratio is (10 to 30): 1, and the ball milling speed is 200 to 450 rpm. After the ball milling process is completed, it is left to stand for 1 to 2 days, and finally the activated Ti-B precursor powder is taken out from the vacuum glove box;
[0011] (4) Mixing and briquetting; the activated Ti-B precursor powder and the Al powder are mixed evenly, and the mixed powder is wrapped with aluminum foil and placed in a mold, and the mixed powder is unidirectionally axially cold pressed to obtain a cylindrical block;
[0012] (5) Reaction process. The aluminum ingot is heated to 850°C-900°C using a pit-type resistance furnace. After the aluminum ingot is completely melted, the block of step (4) is pressed into the graphite bell jar. After the reaction spark appears, the bell jar is taken out for self-propagating reaction. The reaction time is 5-10 minutes. After the reaction is completed, C2Cl6 is pressed into the ingot for refining, stirring, and standing for 5-20 minutes to remove the slag. The stirring and slag removal are repeated 1-2 times. Finally, the melt is poured at 760°C-800°C to obtain a nano Al-TiB2 pure phase intermediate alloy.
[0013] During the ball milling activation treatment of the aforementioned step (3), the mixed powder does not exceed 1 / 2 of the volume of the ball mill. During ball milling, the ball mill is filled with ZrO2 grinding balls with diameters of 4 mm, 8 mm, and 10 mm, respectively, in a ratio of 5:2:1.
[0014] The above-mentioned preferred C2Cl6 is heated at 100℃ for 1h to remove moisture; a layer of coating is applied to the mold and the slag scoop and other tools to prevent Fe impurity elements from contaminating the refiner. A graphite crucible is used for smelting and a graphite rod is used for stirring to prevent Si contamination.
[0015] In the aforementioned step (4) of mixing and briquetting, the activated Ti-B powder precursor powder and the Al powder are mixed evenly, and the nominal density of the subsequently pressed block is 50% to 80%, which is neither too loose nor too compact.
[0016] When the aluminum melt reaches a certain temperature, the powder block obtained in step (4) is pressed into the aluminum melt. After the reaction causes sparks, the bell jar is removed to allow the powder block to undergo a self-propagating reaction.
[0017] The present invention adopts a ball milling-assisted self-propagating reaction preparation process, that is, the original reaction powder is activated by a ball milling process to prepare an activated Ti-B precursor powder, and the preparation of nano TiB2 particles is achieved by combining the traditional self-propagating reaction. The present invention solves the problems of high reaction temperature, incomplete reaction and violent reaction process in the traditional self-propagating synthesis process, which cannot effectively control the size and morphology of nano TiB2 particles. The present invention can fully react at a relatively low reaction temperature, so the TiB2 prepared by the present invention is small and uniform in size. The obtained intermediate alloy is a pure phase, containing only α (Al) and TiB2. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a SEM microstructure image of the nano Al-TiB2 pure phase master alloy prepared by ball milling assisted self-propagating reaction method in Example 1;
[0019] Figure 2 This is a high magnification image of nano Al-TiB2 pure phase master alloy TiB2 particles prepared by ball milling assisted self-propagating reaction method in Example 1;
[0020] Figure 3 The particle size distribution statistics of the nano-Al-TiB2 pure phase master alloy TiB2 prepared by ball milling assisted self-propagating reaction method in Example 1;
[0021] Figure 4 This is the XRD analysis diagram of the nano Al-TiB2 pure phase master alloy prepared by ball milling assisted self-propagating reaction method in Example 1;
[0022] Figure 5 The EDS point analysis results of the nano Al-TiB2 pure phase master alloy TiB2 particles prepared by ball milling assisted self-propagating reaction method in Example 1;
[0023] Figure 6 This is a SEM microstructure image of the nano Al-TiB2 master alloy prepared by the single-substance powder self-propagating reaction method in Comparative Example 1;
[0024] Figure 7 This is a high magnification image of nano Al-TiB2 master alloy TiB2 particles prepared by the single substance powder self-propagating reaction method in Comparative Example 1;
[0025] Figure 8 The particle size distribution of nano Al-TiB2 master alloy TiB2 particles prepared by the single substance powder self-propagating reaction method in Comparative Example 1;
[0026] Fig. 9 The XRD analysis results of the nano Al-TiB2 master alloy prepared by the single substance powder self-propagating reaction method in Comparative Example 1;
[0027] Fig.10 This is a SEM microstructure image of the Al-TiB2 master alloy prepared by the oxide powder self-propagating reaction method in Comparative Example 2;
[0028] Fig.11 This is a high magnification image of the Al-TiB2 master alloy TiB2 particles prepared by the oxide powder self-propagating reaction method in Comparative Example 2;
[0029] Fig.12 This is the particle size distribution diagram of the Al-TiB2 master alloy TiB2 particles prepared by the oxide powder self-propagating reaction method in Comparative Example 2. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments, but the present invention is not limited to the following embodiments:
[0031] Example 1: Preparation of Al-5wt%TiB2 (TiB2 mass fraction is 5%) master alloy by ball milling assisted self-propagating method The preparation process is as follows:
[0032] 1. Raw material preparation: the master alloy is prepared from B powder, Ti powder, Al powder, aluminum ingot, and C2Cl6, wherein the particle size of Al powder is 20-30μm, the particle size of Ti powder is 30-50μm, the particle size of B powder is 1-20μm, the purity of aluminum ingot is 99.99%, and the purity of B powder is 96%. To prepare Al-5wt%TiB2 master alloy, weigh Al powder, Ti powder, B powder and aluminum ingot according to the required proportion, the burnout rate of aluminum ingot is 3%, and the required Al powder: Ti powder: B powder = 1.5: 1: 2 (mol). Weigh 8.63g of B powder, 16.16g of Al powder, 19.12g of titanium powder, and the mass of aluminum ingot is 543.06g.
[0033] 2. Mixing. Put Ti powder and B powder into the mixer and mix them evenly.
[0034] 3. Ball milling activation treatment. The uniformly mixed Ti-B powder is placed in a stainless steel vacuum ball mill, the gas in the ball mill is extracted by a vacuum pump, and vacuum dry ball milling is performed using ZrO2 grinding balls in a planetary high-energy ball mill. The ball milling time is 40 hours, the ball-to-material ratio is 30:1, and the ball milling speed is 400 rpm. After the ball milling process is completed, it is left to stand for 1 day, and finally the activated Ti-B precursor powder is taken out of the vacuum glove box.
[0035] 4. Mixing and briquetting. The activated Ti-B precursor powder and Al powder are mixed evenly, and the mixed powder is placed in a mold, wherein the cylindrical block has a diameter of 62.5 mm, a height of 15 mm, and a nominal density of 60%.
[0036] 5. Apply a layer of coating on the mold and slag scoop, which is a mixture of ZnO and Na2SiO3, to prevent Fe impurity elements from contaminating the refiner. Use a graphite crucible for smelting and a graphite rod for stirring to prevent Si contamination.
[0037] 6. Reaction process. A 543.06 g aluminum ingot was heated to 850°C using a pit-type resistance furnace. After the aluminum ingot was completely melted, a graphite bell was used to press the block of step (4). After the reaction spark appeared, the bell was taken out for self-propagating reaction. The reaction time was 5 min. After the reaction was completed, C2Cl6 was pressed in for refining, stirred, and allowed to stand for 5 min. The slag was removed. The stirring and slag removal were repeated 1-2 times. Finally, the melt was poured at 800°C to obtain a nano Al-TiB2 pure phase intermediate alloy. Figure 1-Figure 3 The SEM microstructure image and particle size statistics of the nano Al-TiB2 pure phase master alloy prepared in Example 1 show that the average size of TiB2 particles is 210 nm, the size is mainly distributed in the range of 150-250 nm, and the particle size distribution is relatively uniform. Figure 4 The XRD analysis results of the nano-Al-TiB2 pure phase master alloy prepared in Example 1 are as follows: Figure 2 As shown, the phases in the intermediate alloy are mainly α(Al) and TiB2 particles, and no diffraction peaks of other reaction by-products are found, indicating that the TiB2 particles prepared in Example 1 have reacted completely and are pure.
[0038] Comparative Example 1
[0039] The process of preparing Al-5wt%TiB2 master alloy by single substance powder self-propagating reaction method is as follows:
[0040] 1. Raw material preparation: the master alloy is prepared from B powder, Ti powder, Al powder, aluminum ingot, and C2Cl6, wherein the purity of the aluminum ingot is 99.9% and the purity of the B powder is 96%.
[0041] 2. To prepare 500g of master alloy, weigh B powder, aluminum powder, titanium powder, and aluminum ingot as required, and the aluminum burnout rate is 3%. The required B powder: Ti powder: Al powder = 2.5: 1.0: 1.5 (mol), weigh 10.36g as required, Al powder 43.08g, titanium powder 30.59g, and the mass of the aluminum ingot is 525.92g.
[0042] 3. Mix Ti powder, B powder and Al powder evenly, put the mixed powder into a mold, and press it into a block.
[0043] 4. Apply a layer of paint to the mold and slag scoop to prevent Fe impurity elements from contaminating the master alloy. Use a graphite crucible for smelting and a graphite rod for stirring to prevent Si contamination.
[0044] 5. Reaction process. A 525.92g aluminum ingot was heated to 880°C using a pit-type resistance furnace. After the aluminum ingot was completely melted, a graphite bell was used to press the block in step 3. After the reaction spark appeared, the bell was taken out for a self-propagating reaction. The reaction time was 5 minutes. After the reaction was completed, C2Cl6 was pressed in for refining, stirred, and allowed to stand for 5 minutes. The slag was removed, and the stirring and slag removal were repeated 1-2 times. Finally, the melt was poured at 780°C to obtain an Al-TiB2 master alloy. Figure 6-Figure 8 The SEM microstructure image and particle size statistics of the Al-TiB2 master alloy prepared in Comparative Example 1 show that the average size of the TiB2 particles is 610 nm, the size distribution is 400-800 nm, and the particle size uniformity is poor. Fig. 9 The XRD analysis results of the Al-TiB2 master alloy prepared in Comparative Example 1 are as follows: Fig. 9 XRD analysis results show that in addition to α(Al) and TiB2 particle phases, the master alloy also contains product-rich Al3Ti phase and incompletely reacted Ti phase, which indicates that the preparation of Al-TiB2 master alloy by self-propagating reaction of single-element powder without ball milling activation has problems of impure products and incomplete reaction.
[0045] Comparative Example 2
[0046] The process of preparing Al-10TiB2 master alloy by oxide powder self-propagating reaction method is as follows:
[0047] 1. Raw material preparation: the master alloy is prepared from H3BO3, TiO2, aluminum powder, titanium powder, aluminum ingot, and C2Cl6, wherein the purity of the aluminum ingot is 99.9%.
[0048] 2. Prepare 1 kg of master alloy, weigh H3BO3, TiO2, aluminum powder, titanium powder, and aluminum ingot as required, and the aluminum burnout rate is 3%. The molar ratio of H3BO3:TiO2:Al powder:Ti powder is required to be 4:1:4:1, and the rest is Al ingot.
[0049] 3. Heat H3BO3 and TiO2 powders at 200℃ for two hours to remove moisture. Take out the powders and stir them every 30 minutes to prevent agglomeration.
[0050] 4. Mix the heated powder with titanium powder and aluminum powder evenly, place the mixed powder in a mold and press it into 15×Φ65mm 3 The columnar powder block has a nominal density of 70%.
[0051] 5. Apply a layer of coating on the mold and slag scoop, which is a mixture of ZnO and Na2SiO3, to prevent Fe impurity elements from contaminating the refiner. Use a graphite crucible for smelting and a graphite rod for stirring to prevent Si contamination.
[0052] 6. Heat the aluminum ingot to 950°C in a pit-type resistance furnace, wait for the aluminum ingot to be completely melted, press the graphite bell into the block of step 4, and take out the bells after the reaction is ignited for a self-propagating direct reaction of the melt for 8 minutes; after the reaction is completed, press in C2Cl6 for refining, stir, let stand for 5 minutes, skim off the slag, and use a skimming spoon to remove the slag and oxide scale on the surface, repeat the stirring, standing and skimming process 1-2 times, and pour the aluminum melt at 850°C into a steel mold preheated to 250°C to obtain an Al-TiB2 master alloy. Figure 10-12 The SEM microstructure image and particle size statistics of the Al-TiB2 intermediate alloy prepared in Comparative Example 2. As shown in the figure, the average size of the TiB2 particles is 1450nm, and the particle size is mainly distributed in the range of 500-2500nm, which are micron-sized ceramic particles with poor uniformity in particle size distribution and irregular particle morphology. This indicates that the efficiency of the oxide powder self-propagating reaction method for preparing nano-sized Al-TiB2 intermediate alloys is low, and the TiB2 particle morphology is poor.
Claims
1. A nano-scale Al-TiB2 pure phase master alloy prepared by ball milling assisted self-propagating method, characterized in that: The physical phase composition includes α(Al) and TiB2; the preferred average particle size of TiB2 is 210nm, the particle size distribution is 150-250nm, the particle size distribution of TiB2 particles is uniform, and the morphology is regular.
2. The method for preparing nano-scale Al-TiB2 pure phase master alloy by ball milling assisted self-propagating method according to claim 1, characterized in that: The following steps are involved: (1) Raw material preparation: weigh Al powder, Ti powder and B powder according to the required proportion, wherein the molar ratio of Al powder: Ti powder: B powder = (1.0-2.5): (0.5-2.0): (1-4), wherein the particle size of Al powder is 20-30 μm, the particle size of Ti powder is 30-50 μm, the particle size of B powder is 1-20 μm, the purity is (96%), and the purity of aluminum ingot is 99.9%; (2) Mixing: Place Ti powder and B powder in a mixer and mix them evenly; (3) ball milling activation treatment, the uniformly mixed Ti powder and B powder are placed in a stainless steel vacuum ball mill, the gas in the ball mill is extracted by a vacuum pump, and vacuum dry ball milling is performed using ZrO2 grinding balls in a planetary high-energy ball mill, wherein the ball milling time is 10 to 50 hours, the ball-to-material ratio is (10 to 30): 1, and the ball milling speed is 200 to 450 rpm. After the ball milling process is completed, it is left to stand for 1 to 2 days, and finally the activated Ti-B precursor powder is taken out from the vacuum glove box; (4) Mixing and briquetting; the activated Ti-B precursor powder and the Al powder are mixed evenly, and the mixed powder is wrapped with aluminum foil and placed in a mold, and the mixed powder is unidirectionally axially cold pressed to obtain a cylindrical block; (5) Reaction process. The aluminum ingot is heated to 850°C-900°C using a pit-type resistance furnace. After the aluminum ingot is completely melted, the block of step (4) is pressed into the graphite bell jar. After the reaction spark appears, the bell jar is taken out for self-propagating reaction. The reaction time is 5-10 minutes. After the reaction is completed, C2Cl6 is pressed into the ingot for refining, stirring, and standing for 5-20 minutes to remove the slag. The stirring and slag removal are repeated 1-2 times. Finally, the melt is poured at 760°C-800°C to obtain a nano Al-TiB2 pure phase intermediate alloy.
3. The method according to claim 2, characterized in that The mass percentage of the aluminum ingot is 90.5-93.0%, and the total mass percentage of Al powder, Ti powder and B powder is 6%-9.5%.
4. The method according to claim 2, characterized in that During the ball milling activation treatment in step (3), the mixed powder does not exceed 1 / 2 of the volume of the ball mill. During ball milling, the ball mill is filled with ZrO2 grinding balls with diameters of 4 mm, 8 mm, and 10 mm, respectively, in a ratio of 5:2:
1.
5. The method according to claim 2, characterized in that The C2Cl6 is heated at 100°C for 1 hour to remove moisture; a layer of coating is applied to the mold and the slag scoop to prevent Fe impurity elements from contaminating the refiner. A graphite crucible is used for smelting and a graphite rod is used for stirring to prevent Si contamination.
6. The method according to claim 2, characterized in that In the mixing and briquetting process of step (4), the activated Ti-B powder precursor powder and the Al powder are mixed evenly, and the nominal density of the subsequently pressed block is 50% to 80%, which is neither too loose nor too compact.
7. The method according to claim 2, characterized in that When the aluminum melt reaches a certain temperature, the powder block obtained in step (4) is pressed into the aluminum melt. After the reaction causes sparks, the bell jar is removed to allow the powder block to undergo a self-propagating reaction.
8. The method according to claim 2, characterized in that Step (1) The molar ratio of Ti powder to B powder is 1:2.